Effect of nitrogen sources on some morphological characteristics of in vitro stevia rebaudiana Bertoni - Akbari, F.; Arminian, A.; Kahrizi, D.; Fazeli, A. (Cellular and Molecular Biology, 2017)
Stevia rebaudiana Bertoni belongs to Asteraceae family that leaves 200-300 times sweeter than sugar. Low seed fertility is one of the most important problems in Stevia production. So, Plant tissue culture is an efficient method for mass propagation of Stevia. In this research, we studied the effect of various concentrations of nitrogen on some morphological traits of stevia under in vitro conditions. We used axillary nodes as explants and they were cultured on Murashige and Skoog (MS) medium containing inorganic nitrogen sources i.e. NH4NO3(0, 825 and 1650 mg/l), KNO3(0, 950 and 1900 mg/l) were observed. The cultures were kept for 4 weeks at a temperature of 25±2°C with a photoperiod of 16/8 hour low light/dark each day. Maximum shoot length (89.33 mm), dry weight of plants (0.10 mg) and leaf fresh weight (0.42 mg) was observed on MS medium with 1650 mg/l NH4NO3 and 950 mg/l KNO3. Minimum shoot length (6.13 mm), root length (6.60 mm), leaf number (4.26), leaf dry weight (0.01 mg), leaf fresh weight (0.05 mg), total dry and fresh weight (0.02 and 0.15 mg) and growth rate was observed on a MS medium without nitrogen sources. Moreover, presence of nitrogen sources increases both shooting and rooting in Stevia rebaudiana Bertoni.